PENINGKATAN HASIL BELAJAR IPA MATERI CAHAYA DAN ALAT OPTIK MELALUI MODEL DISCOVERY LEARNING: STUDI PENELITIAN TINDAKAN KELAS - Yanuarsi, Wiwik Eka (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2023)
This study aims to describe the level of science learning outcomes in students of class VIIID SMPN 1 Tempuran in the 2021/2022 academic year after the implementation of the Discovery learning model. This research is class action research (PTK). Each cycle consists of three stages of activities, namely planning, action implementation and observation, and reflection. The subjects of this study were students of class VIIID SMPN 1 Tempuran Magelang Regency with a total of 32 students. Data collection in this study used teacher and student activity observation sheets and written tests. Data analysis techniques used were descriptive qualitative and descriptive quantitative with percentages. The results showed an increase in science learning outcomes of Light and Optical Instruments material in students of class VIII D SMP Negeri 1 Tempuran after the implementation of learning with the Discovery learning model in cycle I on average was 76.5 after cycle II on average was 83.3. Behavioral changes that occur in students of class VIID SMP Negeri 1 Tempuran in the implementation of learning with the Discovery learning model to improve science learning outcomes of Light and Optical Devices material, among others, are as follows (a) students are more able to cooperate; (b) students are more active; (c) students are more responsible; (d) students are more disciplined.